Analysis of global research hotspots and trends in immune cells in intervertebral disc degeneration: A bibliometric study - Nan Wang; Zehua Mi; Shuang Chen; Xiaoyang Fang; Zhipeng Xi; Wenqiang Xu; Lin Xie (Human Vaccines & Immunotherapeutics)
Intervertebral disc degeneration is an important pathological basis for spinal degenerative diseases. The imbalance of the immune microenvironment and the involvement of immune cells has been shown to lead to nucleus pulposus cells death. This article presents a bibliometric analysis of studies on immune cells in IDD in order to clarify the current status and hotspots. We searched the WOSCC, Scopus and PubMed databases from 01/01/2001 to 08/03/2023. We analyzed and visualized the content using software such as Citespace, Vosviewer and the bibliometrix. This study found that the number of annual publications is increasing year on year. The journal study found that Spine had the highest number of articles and citations. The country/regions analysis showed that China had the highest number of publications, the USA had the highest number of citations and total link strength. The institutional analysis found that Shanghai Jiao Tong University and Huazhong University of Science Technology had the highest number of publications, Tokai University had the highest citations, and the University of Bern had the highest total link strength. Sakai D and Risbud MV had the highest number of publications. Sakai D had the highest total link strength, and Risbud MV had the highest number of citations. The results of the keyword analysis suggested that the current research hotspots and future directions continue to be the study of the mechanisms of immune cells in IDD, the therapeutic role of immune cells in IDD and the role of immune cells in tissue engineering for IDD.